ANNULMENT OF MARRIAGE DUE TO DATA MANIPULATION IN THE PERSPECTIVE OF ISLAMIC LAW AND POSITIVE LAW - Nursheta Resmi, Herni; Hidayah, Astika Nurul (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
Abstract Marriage is a sacred bond between a man and a woman whose aim is to form a happy and eternal family based on the Almighty Godhead. However, in practice, sometimes marriages are annulled for several reasons, one of which is due to data manipulation. This research aims to analyze marriage annulments due to data manipulation from the perspective of Islamic law and positive law. The method used in this research is normative juridical, namely the research process of researching and studying law as norms, rules, legal principles, legal principles, legal doctrine, legal theory and other literature to answer the legal problems being studied. The research results show that in Islamic law, data manipulation in marriage is considered fraud (gharar) which can damage the purpose of marriage, so it can be a reason to cancel the marriage. Meanwhile, in positive law in Indonesia, data manipulation in marriage is regulated in the Marriage Law and the Compilation of Islamic Law as one of the reasons for canceling a marriage. So, both in Islamic law and positive law in Indonesia, manipulation of data in a marriage can be a reason to annul a marriage. Keywords: Marriage, Marriage Cancellation, Data Manipulation